Antimicrobial Activity of Pentaamminecobalt(III) Complexes of α-Amino Acids - Thaminum Ansari, A.; Subramani, K. (Asian Journal of Chemistry, 2010)
Pentaamminecobalt(III) complexes of a-amino acids were synthesized. The antimicrobial activity of these complexes were tested with bacteria like E. coli, S. aureus, Salmonella, Pseudomonas, Klebsiella and fungi like A. niger, Penicillium. The minimum inhibitory concentration of these complexes against microorganism were estimated by turbidity methods.